Endothelial Jagged1 Antagonizes Dll4 Regulation of Endothelial Branching and Promotes Vascular Maturation Downstream of Dll4/Notch1. Issue 5 (May 2015) - Pedrosa, Ana-Rita; Trindade, Alexandre; Fernandes, Ana-Carina; Carvalho, Catarina; Gigante, Joana; Tavares, Ana Teresa; Diéguez-Hurtado, Rodrigo; Yagita, Hideo; Adams, Ralf H.; Duarte, António
Abstract : Objective—: Notch signaling controls cardiovascular development and has been associated with several pathological conditions. Among its ligands, Jagged1 and Dll4 were shown to have opposing effects in developmental angiogenesis, but the underlying mechanism and the role of Jagged1/Notch signaling in adult angiogenesis remain incompletely understood. The current study addresses the importance of endothelial Jagged1-mediated Notch signaling in the context of adult physiological angiogenesis and the interactions of Jagged1 and Dll4 on angiogenic response and vascular maturation processes. Approach and Results—: The role of endothelial Jagged1 in wound healing kinetics and angiogenesis was investigated with endothelial-specific Jag1 gain-of-function and loss-of-function mouse mutants ( eJag1 OE and eJag1c KO). To study the interactions between the 2 Notch ligands, genetic mouse models were combined with pharmacological inhibition of Dll4 or Jagged1, respectively. Jagged1 overexpression in endothelial cells increased vessel density, maturation, and perfusion, thus accelerating wound healing. The opposite effect was seen in e Jag1 cKO animals. Interestingly, Dll4 blockade in these animals led to an increase in vascular density but induced a greater decrease in perivascular cell coverage. However, Jagged1 inhibition in Dll4 gain-of-function (e Dll4 OE) mutants, with reduced angiogenesis, further diminished angiogenic growth and hampered perivascular cell coverage. Our findings suggest that as Dll4 blocks endothelial activation through Notch1 signaling, it also induces Jagged1 expression. Jagged1 then blocks Dll4 signaling through Notch1, allowing endothelial activation by vascular endothelial growth factor and endothelial layer growth. Jagged1 also initiates maturation of the newly formed vessels, possibly by binding and activating endothelial Notch4. Importantly, mice administered with a Notch4 agonistic antibody mimicked the mural cell phenotype of e Jag1 OE mutants without affecting angiogenic growth, which is thought to be Notch1 dependent. Conclusions—: Endothelial Jagged1 is likely to operate downstream of Dll4/Notch1 signaling to activate Notch4 and regulate vascular maturation. Thus, Jagged1 not only counteracts Dll4/Notch in the endothelium but also generates a balance between angiogenic growth and maturation processes in vivo. Abstract : Supplemental Digital Content is available in the text.